1989
DOI: 10.1038/jcbfm.1989.88
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the NMDA Antagonist MK-801 on Local Cerebral Blood Flow in Focal Cerebral Ischaemia in the Rat

Abstract: The effects of MK-801 upon local CBF after permanent middle cerebral artery (MCA) occlusion have been examined using [14C]iodoantipyrine autoradiography in halothane-anaesthetised rats. MK-801 (0.5 mg kg-1 i.v.) or saline was administered 30 min before MCA occlusion and CBF measured approximately 40 min after occlusion. In the hemisphere contralateral to the occluded MCA, MK-801 significantly reduced local CBF in 19 of the 22 regions examined from the levels in saline-treated rats. In the contralateral hemisph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Other authors have also shown that the neuroprotective effects of agents acting either at the NMDA receptor complex (e.g. dizolcipine (MK-801), Stevens and Yaksh, 1990;Park et al, 1989;kynurenic acid, Seylaz et al, 1990), adenosine A 1 receptors (Seylaz et al, 1990) or calcium channels (Hakim, 1986)) may be independent of postischemic blood flow in both focal (Hakim, 1986;Park et al, 1989) and global (Stevens and Yaksh, 1990;Seylaz et al, 1990) ischemia. It appears, therefore, that 'hemodynamic protection' (Nakayama et al, 1988) during the immediately postocclusive period may be less critical than prevention of the metabolic derangement of the ischemic brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also shown that the neuroprotective effects of agents acting either at the NMDA receptor complex (e.g. dizolcipine (MK-801), Stevens and Yaksh, 1990;Park et al, 1989;kynurenic acid, Seylaz et al, 1990), adenosine A 1 receptors (Seylaz et al, 1990) or calcium channels (Hakim, 1986)) may be independent of postischemic blood flow in both focal (Hakim, 1986;Park et al, 1989) and global (Stevens and Yaksh, 1990;Seylaz et al, 1990) ischemia. It appears, therefore, that 'hemodynamic protection' (Nakayama et al, 1988) during the immediately postocclusive period may be less critical than prevention of the metabolic derangement of the ischemic brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In conscious rats, MK-801 increases local CBF in specific regions including neocortex and caudate nucleus (Nehls et al, 1990;Roussel et al, 1992), while in artificially-ventilated, anaesthetized rats MK-801 induces widespread homogeneous reductions in CBF (Park et al, 1989). However MK-801 does not induce further reductions in CBF in the ischaemic core (Park et al, 1989;Greenberg et al, 1991 reported a beneficial action of MK-801 treatment initiated prior to or during the ischaemic phase of transient MCA occlusion in the normotensive rat (Yang et al, 1991;Buchan et al, 1992). However in these models the rats were conscious for most of the ischaemic period and the reduction in damage observed with MK-801 has been attributed to an increase in CBF in the ischaemic core region rather than a direct anti-excitotoxic action (Buchan et al, 1992).…”
Section: Physiological Variablesmentioning
confidence: 98%
“…Thus the lower blood pressure at onset of MCA occlusion in the 1 h MK-801 group appears to have increased the severity of the ischaemic insult and directly counteracted the neuroprotective action of the drug. In addition to its peripheral action on blood pressure, MK-801 has marked effects on CBF which differ in conscious and anaesthetized animals (Park et al, 1989;Nehls et al, 1990;Roussel et al, 1992) and which could potentially influence outcome following cerebral ischaemia. In conscious rats, MK-801 increases local CBF in specific regions including neocortex and caudate nucleus (Nehls et al, 1990;Roussel et al, 1992), while in artificially-ventilated, anaesthetized rats MK-801 induces widespread homogeneous reductions in CBF (Park et al, 1989).…”
Section: Physiological Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Spreading depression can be blocked by glutamate antagonists (Marrannes et al, 1988), and the same drugs are also able to reduce the size of an infarct following permanent MCA occlusion (Ozyurt et al, 1988;Park et al, 1988;Dirnagl et al, 1990). Inter estingly, the therapeutic effect is not associated with any changes in blood flow (Park et al, 1988(Park et al, , 1989, indicating that the drugs do not interfere with oxygen delivery to the tissue.…”
mentioning
confidence: 99%